Error Analysis of Students in Solving Algebraic Expression Problems Using the Newman Procedure - Dhani, Widiyah Rahma; Nurrahmawati , Nurrahmawati; Afri , Lusi Eka; Khan, Muhammad Ali (International Journal of Applied Learning and Research in Algebra, 2025)
This research aims to determine the forms of errors made by class VIII students of SMPN 3 Rambah Hilir in solving algebraic operations material questions based on Newman’s procedure. This research employs a descriptive qualitative approach. The subjects in this research were class VIII SMPN 3 Rambah Hilir. The research instrument uses tests and interviews. Based on the results of data analysis, it was concluded that students made (1) errors in reading the questions of  100% in the form of not knowing the meaning of the questions; (2) errors in understanding the questions of 26,7% in the form of not knowing what to look for; (3) mistakes transforming questions amounted to 50,0% in the form of not being able to determine the mathematical operations and formulas used to solve the problem; (4)errors in process skills amounting to 64,4% in the form of errors in calculations with; (5) errors in writing the final answer amounting to 68,9% consist of errors in writing the final answer and not making a conclusion.